Assessment of information and communication technology (ICT) competence and literacy skills among undergraduates as a determinant factor of academic achievement - (:unkn) unknown (My University, 2018)
Almost every human endeavor is supported or driven by Information and Communication Technology (ICT) including education. Teaching, learning, assessment, course registration, payment among other things are now ICT-based. Humans have attempted to use technology to improve their life span and quality, and education is not excempted in this great paradigm shift. This paper focuses on the Information and Communication Technology competence and literacy skills of undergraduate students in Ogun State, using their information literacy skills/competence as determinants of their academic achievement. A descriptive survey design was adopted for this study. The population of the study consists of 10,713 students from Tai Solarin University of Education (TASUED) comprising 4 colleges and 10,000 students of Babcock University comprising 9 colleges. Simple random sampling was used for the selection of a sample of 170 respondents from Babcock University and 130 respondents from TASUED. Three hundred stdents (from 100-500 levels) were the sample of the study. Well-structured questionnaire was the main instrument used for the collection of primary data. The findings of this study show that 80% of the undergraduate students of TASUED and BU have basic ICT literacy skills which entail the ability to source for and access information resources for their research. Furthermore, this study has proved that the use of ICT has improved students' academic performance. Recommendations were made based on the findings from the study.
Keywords: African Research